Personality Traits Induce Different Brain Patterns When Processing Social and Valence Information - Hevia-Orozco, Jorge Carlos; Reyes-Aguilar, Azalea; Hernández-Pérez, Raúl; González-Santos, Leopoldo; Pasaye, Erick H.; Barrios, Fernando A. (Frontiers in Psychology, 2022)
This paper shows the brain correlates of Cloninger’s personality model during the presentation of social scenarios under positive or negative valence situations. Social scenarios were constructed when participants played the Dictator game with two confederates that had two opposites roles as the cooperator (Coop) and non-cooperator (NoCoop). Later the same day during an fMRI scanning session, participants read negative (Neg) and positive (Pos) situations that happened to confederates in the past. Participants were asked to think “how do you think those people felt during that situation?”. A dissimilarity matrix between stimuli was obtained from fMRI results. Results showed that Harm Avoidance trait people make use of right middle frontal gyrus and left superior frontal gyrus to discriminate between Coop and NoCoop. Cooperation as a trait makes use of the right superior temporal gyrus and the right precuneus to discriminate between Coop and NoCoop in positive social scenarios. Finally, Self-directedness trait people make use of the right inferior parietal lobe to discriminate between Coop and NoCoop in negative social scenarios and the right precuneus to discriminate between Coop and Strangers. An intuitive link between discrimination findings and behavioral patterns of those personality traits is proposed.